Geospatial Technologies and Homeland Security Research Frontiers and Future Challenges - Sui, Daniel (GeoJournal Library, 2008)
This edited volume, based upon the papers presented during the "Geospatial Technologies and Homeland Security Symposium" on Nov. 15, 2006, presents an overview of the latest development of geospatial technologies (including, but not limited to, GIS, RS, GPS, LBS, spatial analysis and modelling etc.) and their applications in piecing together the complex puzzles facing the challenges of the homeland security research and education. A wide variety of topics, ranging from conceptual and methodological to technical and social/legal issues, are covered by contributions from leading academic researchers. This book will be of great interest to researchers and practitioners in both GIS and homeland security. It could also serve as a reference text for advanced GIS courses at the undergraduate level or main text for seminars in GIScience.